Human pluripotent stem cell–derived neuronal progenitor cells promote neurogenesis and functional recovery by attenuating neuroinflammation and via extracellular vesicles in a subacute stroke model - Kim, Hyun-Jin; Kim, Dong Hee; Choi, Jee In; Sim, Hye Ryeong; Jung, Sangyong; Hwang, Dong-Youn; Kim, MinYoung (Frontiers in Immunology, 2025)
IntroductionStroke remains a leading cause of long-term disability worldwide. The limited therapeutic window of current treatments underscores the need for alternative regenerative strategies. Neural progenitor cells (NPCs) are promising candidates for brain repair. However, the optimal timing of therapy and the mechanisms underlying its effects on ischemic stroke remain unclear.MethodsTo evaluate their efficacy, NPCs were administered intravenously to a subacute stroke (day 7) rat model. The outcomes were determined by comparison with saline treatment using neurobehavioral assessments, infarct volume measurements, and molecular assays. In addition, NPC secretome profiling was performed to assess the underlying cellular mechanisms.ResultsThe NPC group showed significant improvement in motor function at 3 weeks post-injection (p<0.001) and reduced infarct volume (p<0.05). Immunofluorescence analysis revealed increased BrdU/DCX colocalization in the subventricular zone on day 14 (p<0.05). Western blotting confirmed the upregulation of NeuN (p<0.01), Nestin (p<0.05), and DCX (p = 0.0668) in the ipsilesional brain on day 28. The neuroprotection-related pathways revealed elevated protein levels of phosphorylated Akt, GSK3β, Erk, and CREB (p<0.05). Secretome profiling of NPC-conditioned medium and extracellular vesicles identified key regenerative factors such as Angiopoietin-1, BDNF, bFGF, MMP2, EGF, and VEGFa.DiscussionNPC administration during the subacute phase of stroke promoted functional recovery by promoting neurogenesis and modulating key survival pathways. These results highlight the therapeutic potential of NPCs as cell-based interventions for delayed stroke treatment and provide mechanistic insights into their reparative effects.